Genetic amelioration of fruit and vegetable crops to increase biotic and abiotic stress resistance through CRISPR Genome Editing - Sardar, Atish (Frontiers in Plant Science, 2023)
Environmental changes and increasing population are major concerns for crop production and food security as a whole. To address this, researchers had focussed on the improvement of cereals and pulses and have made considerable progress till the beginning of this decade. However, cereals and pulses together, without vegetables and fruits, are inadequate to meet the dietary and nutritional demands of human life. Production of good quality vegetables and fruits is highly challenging owing to their perishable nature and short shelf life as well as abiotic and biotic stresses encountered during pre-and post-harvest. Genetic engineering approaches to produce good quality, to increase shelf life and stressresistance, and to change the time of flowering and fruit ripening by introducing foreign genes to produce genetically modified crops were quite successful. However, several biosafety concerns, such as the risk of transgene-outcrossing, limited their production, marketing, and consumption. Modern genome editing techniques, like the CRISPR/Cas9 system, provide a perfect solution in this scenario, as it can produce transgene-free genetically edited plants. Hence, these genetically edited plants can easily satisfy the biosafety norms for crop production and consumption. This review highlights the potential of the CRISPR/Cas9 system for the successful generation of abiotic and biotic stress resistance and thereby improving the quality, yield, and overall productivity of vegetables and fruits.